The Effects of Bone Marrow Stromal Cells Therapy on the Improvement of Epilepsy Model in Rat Induced by pilocarpine - Ali Reza Abdani-Pour (Journal of Rehabilitation, 2008)
Objective: Temporal lobe epilepsy is the most common type of epilepsy in adult humans, which is characterized clinically by a progressive development of spontaneous recurrent seizures of temporal lobe origin. Because of the side effects of current treatment protocols, the resistance to pharmacological therapy in this investigation, bone marrow stromal cells were used to evaluate the recovery of epileptic rats induced by pilocarpine.